A Study of Primary Skin Closure by Intradermal Stitches with and Without Adhesive Tapes (Bangladesh Journal of Plastic Surgery, 2013)
The study was done to evaluate whether adhesive tape after intradermal skin closure in face and neck produces better aesthetic scar than intradermal skin closure in face and neck without adhesive tape. It was a prospective, interventional, purposive study and was done in department of Plastic Surgery, Dhaka Medical College Hospital (D.M.C.H.) from July 2005 to October 2007. A total of 90 patients was included in the study. In one group (A), face and neck skin was closed by intradermal stitches with Vicryl. In other group (B), face and neck skin was closed by intradermal stitches with Vicryl 6/0, cutting body needle with adhesive tape (Nichistrip). The study included 76 patients. The age range was from 13-45 years. 34 patients were male and 42 patients were female. None of the baseline variables like age and gender was found to be different in two groups (p> 0.05). There was no statistically significant difference between two groups in the distribution of Incision along Langers line, Length of incisions, Gapping and Swelling (p>0.05). Group B (intradermal skin closure in face and neck lesions with adhesive tape) had statistically highly significant difference (p